Impulsiveness, anger and power strategies as predictors of partner violence with female perpetrators. - Galindo Moto, Manuel Alejandro (Consorcio de Universidades Mexicanas A.C., 2021)
Anger, impulsiveness and power strategies had not been used to predict physical, psychological, social, economic and sexual partner violence with female perpetrators. Therefore, variables were used as predictors in a non-probabilistic sample of 532 women from the city of Puebla (X = 26.27 of age, SD = 9.67). Multiple step regressions were used for this study. An R² of .40 was obtained for psychological/physical violence with variables of manipulation and blackmail, dominance, angry reaction, automatism, gratification and angry temperament. Manipulation and blackmail, angry reaction, dominance, gratification and automatism were used as predictors of economic/social violence, obtaining an R² of .19. In sexual violence, results showed low explained variances. It is suggested that physical, psychological, economic and social violence share the same causes.